Enhancing Confidence and Fluency through Project Based Learning for Basic Speaking Course - Agustina, Diyah Dwi; Supatmi , Ruri; Prestika , Aulfa Reyza Ayuni; Cahyani , Asti Nur (Journal Corner of Education, Linguistics, and Literature, 2025)
This study investigates how Project-Based Learning can effectively improve students’ confidence and speaking fluency in a Basic Speaking course. Speaking is often considered one of the most difficult language skills to master due to factors such as nervousness and limited speaking opportunities. Through the application of PBL, learners participate in purposeful, group-oriented activities that encourage the practical use of the target language in realistic situations. The subject of this study wa the second semester students of English Education Department, Nahdlatul Ulama Lampung University. This study was utilizing a Classroom Action Reseach method that includes problem identification, planning, action, observation and reflection. The data collecting used triangulation consist of test, observation and interviews. The study in Cycle 1 and Cycle 2 reveals that Project Based Learning contributes to a positive and motivating learning atmosphere. It also enhances students’ engagement and facilitates frequent opportunities for genuine interaction. Consequently, students exhibit significant enhancement in both their confidence and fluency in speaking. The findings suggest that PBL is an effective instructional approach for cultivating communicative abilities in beginning language learners. Keywords: